THE ROLE OF HIGH-FREQUENCY VENTILATION IN THE TREATMENT OF ACUTE RESPIRATORY DISTRESS SYNDROME IN NEWBORNS IN THE POSTOPERATIVE PERIOD OF CARDIAC SURGERY (Herald of the National Children's Medical Center, 2025)
Acute Respiratory Distress Syndrome (ARDS) In newborns with congenital heart defects (CHD), it is a severe and life-threatening complication of the postoperative period. It significantly worsens the clinical prognosis, requiring effective and gentle respiratory support methods. One of the promising approaches is high-frequency oscillatory ventilation, which allows achieving adequate gas exchange with minimal barotrauma.